Legality of Abortion by Rapes Perspective of Islamic Law, Indonesian Positive Law and Human Rights - Moh. Manaf Badri; Muhibbin Muhibbin (Budapest International Research and Critics University, 2022)
Promiscuity between men and women outside of marriage, especially students and college students, has now reached a very worrying limit. This is due to the weakening of religious values in people's lives, coupled with the development of information technology, which makes it easier to access various kinds of information, sometimes misused by children or teenagers. In addition, the incessant mass media that offers a glamorous, free and all-hedonistic life that causes the younger generation to be dragged into the brink of collapse. with the development of the times, many young people's morals are starting to erode and do things that are not appropriate to do, like this abortion. some formulations of the problem, namely how to legalize abortion for rape victims in Indonesia according to Law number 36 of 2009 concerning Health? What is the Concept of Abortion for Rape Victims from the Perspective of Islamic Law, Criminal Law and Human Rights? This study uses normative legal research methods, and by using a statutory approach and a philosophical legal approach. The health Law if we relate to abortion due to pregnancy due to rape, it can be concluded that in general the practice of abortion is prohibited, but the prohibition is excluded in several circumstances such as pregnancy due to rape. Islamic law in this case can be judged to be permissible if the abortion resulting from the act of adultery is permissible as long as it is still in the form of nutfah or 'alaqah, that is, not yet eighty days. Then there is an emergency which would otherwise endanger the life of his mother.